The Effect of Workload, Work Environment and Work Discipline on Employee Performance at UD. Laksana Profile - Kireina, Ni Putu Neska; Marini, Putu Lidia; Gayatri, I Gusti Agung Sasih (Business Management, 2025)
This study aims to determine the effect of workload, work environment, and work discipline on employee performance. This study uses an associative quantitative approach with data collection through questionnaires distributed to 47 respondents in the UD. Laksana Profile environment. Data analysis techniques used include validity tests, reliability, classical assumptions, multiple linear regression, T-test, and F-test. The results of the study indicate that partially and simultaneously the variables of workload, work environment, and work discipline have a positive and significant effect on employee performance. This study implies the importance of paying attention to workload, work environment, and monitoring discipline to support optimal productivity and performance.